Global marketing - Keegan, Warren J.; Green, Mark C. (Upper Saddle River, N.J. : Prentice-Hall, 1997)
This book is about global marketing. An organization that engages in global marketing focuses its resources on global market opportunities and threats.
Keywords: Marketing; Management; Export marketing -- Management; Export marketing -- Management -- Case studies